2008
DOI: 10.1111/j.1744-313x.2008.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CTLA‐4 and CD28 gene polymorphisms in a group of Turkish patients with colorectal cancer

Abstract: Colorectal cancer (CRC), also called colon cancer or bowel cancer, includes cancerous growths in the colon, rectum and appendix. The immune system is an important defence mechanism against cancer and is often dysfunctional in patients with malignancies. Cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) and CD28 genes encode receptors that provide negative and positive signals, respectively. Polymorphisms in these genes can affect their functions. In this study, we aimed to investigate the association of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 29 publications
0
37
2
2
Order By: Relevance
“…Moreover, it was found by us and others that the same allele confers susceptibility to female-related cancers: sporadic breast cancer [31,48], and cervical cancer [29,32] as well as non-small cell lung cancer in women [24]. In contrast to our results CTLA-4g.319C>T polymorphism was not associated with lung cancer (without stratification by gender) [41] or other cancers, such as colon cancer [42], colorectal cancer [52] or multiple myeloma [44]. The meta-analysis performed by Zhang et al [49] indicated this polymorphism as related to cancer risk in the Europeans.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, it was found by us and others that the same allele confers susceptibility to female-related cancers: sporadic breast cancer [31,48], and cervical cancer [29,32] as well as non-small cell lung cancer in women [24]. In contrast to our results CTLA-4g.319C>T polymorphism was not associated with lung cancer (without stratification by gender) [41] or other cancers, such as colon cancer [42], colorectal cancer [52] or multiple myeloma [44]. The meta-analysis performed by Zhang et al [49] indicated this polymorphism as related to cancer risk in the Europeans.…”
Section: Discussioncontrasting
confidence: 56%
“…Ethnic disparities like these do exist with respect to the prevalence of a polymorphism in a particular ethnic population and its association with a disease (Mandal et al, 2010). For example, CTLA-4 +49 G/A polymorphism is known to be associated with the risk of colorectal cancer in Chinese but no such association was seen in a study on Turkish patients (Dilmec et al, 2008;Qi et al, 2010). This SNP was also found to be not associated with colorectal neoplasm among Italian Caucasians (Solerio et al, 2005).…”
Section: 2035 Lack Of Any Association Of the Ctla-4 +49 G/a Polymorpmentioning
confidence: 95%
“…Taq1 gene polymorphism genotypes frequencies differ among different ethnicities, different cancer types (Bid et al, 2005), and methodology by which Taq1 VDR polymorphism was investigated, sample size and vitamin D serum levels (Onen et al, 2008). Among Indian individuals the frequencies of Taq1 variants were 49%, 43% and 8% (Bhanushali et al, 2010) while Japanese study showed 77%, 22% and 1% (Minamitani et al, 1998) and a Turkish, study showed frequency of 40.8%, 47.9% and 11.2% (Dilmec et al, 2009) for TT, Tt and tt respectively.…”
Section: Discussionmentioning
confidence: 99%